Effect of Al2O3 on the Formation of Calcium Ferrite in the Solid State - Kaikai Bai; Jiangwei Shen; Zhenglu Zhu; Haibin Zuo; Yuzhu Pan; Jingsong Wang; Qingguo Xue (Metals, 2019)
Pure chemical reagents Fe2O3, Al2O3, and Ca(OH)2 were used to investigate the formation of calcium ferrite in the solid state. The phase composition of the prepared samples was determined using X-ray powder diffraction and by SEM. The TG-DSC analysis was performed to analyze the decomposition behavior and formation of calcium ferrites. The formation rate of calcium ferrite was determined by in-situ X-ray diffraction (XRD) and by the K-value method. The X-ray diffraction analysis was performed using Pt as the internal standard for application of the K-value method. The formation of Ca2Fe2O5 (C2F) occurred much earlier than the formation of CaFeO4 (CF). C2F and CF were formed at approximately 600 °C and 700−800 °C, respectively. With an increase of Al2O3 content, there was a tendency to decrease the melting temperature. There was a heating scheme in this study (i.e., 10 °C per minute to 1250 °C under a flowing atmosphere of high-purity air). The total amount of CF increased with an increase of the Al2O3 content, and the Al2O3 content reaching the maximum value of CF was 1.4%. As the Al2O3 content increased from 1.4% to 2.8%, the total amount of CF reduced slightly. When the Al2O3 concentration was greater than 2.8%, the content of CF generated significantly decreased with the increase of Al2O3.